Complete Genome Sequence of Dengue Virus Serotype 3 from Guangzhou, China - Bai, Zhijun (American Society for Microbiology, 2013)
In 2009, dengue virus serotype 3 (DENV-3) was first detected in Guangzhou, China. In this study, we identified another isolated strain belonging to genotype II. Phylogenetic analysis shows that the GZ/10476/2012 strain has a close relationship with the DENV-3 genotype II from Southeast Asian strains.